Genome-wide transcriptional analyses of Clarireedia jacksonii isolates associated with multi-drug resistance - Huangwei, Zhang; Peiyuan, Jin; Yixuan, Kong; Zhimin, Yang; Yuxin, Zhou; Geunhwa, Jung; Jian, Hu (Frontiers in Microbiology, 2023)
Emerging multidrug resistance (MDR) in Clarireedia spp. is a huge challenge to the management of dollar spot (DS) disease on turfgrass. Insight into the molecular basis of resistance mechanisms may help identify key molecular targets for developing novel effective chemicals. Previously, a MDR isolate (LT586) of C. jacksonii with significantly reduced sensitivities to propiconazole, boscalid, and iprodione, and a fungicide-sensitive isolate (LT15) of the same species were isolated from creeping bentgrass (Agrostis stolonifera L.). The present study aimed to further explore the molecular mechanisms of resistance by using genome-wide transcriptional analyses of the two isolates. A total of 619 and 475 differentially expressed genes (DEGs) were significantly down and upregulated in the MDR isolate LT586, compared with the sensitive isolate LT15 without fungicide treatment. Three hundreds and six and 153 DEGs showed significantly lower and higher expression in the MDR isolate LT586 than those in the sensitive isolate LT15, which were commonly induced by the three fungicides. Most of the 153 upregulated DEGs were xenobiotic detoxification-related genes and genes with transcriptional functions. Fifty and 17 upregulated DEGs were also commonly observed in HRI11 (a MDR isolate of the C. jacksonii) compared with the HRS10 (a fungicide-sensitive isolate of same species) from a previous study without and with the treatment of propiconazole, respectively. The reliability of RNA-seq data was further verified by qRT-PCR method using a few select potentially MDR-related genes. Results of this study indicated that there were multiple uncharacterized genes, possibly responsible for MDR phenotypes in Clarireedia spp., which may have important implications in understanding the molecular mechanisms underlying MDR resistance.